Engaging with China: The Higher Education Dilemma - Altbach, Philip; de Wit, Hans (International Higher Education, 2021)
Academic relations with China have become a fraught and controversial topic globally. Of course, “it takes two to tango”—and if insurmountable challenges are set up and negative policies and practices are implemented (from either the Chinese side or the other side), then engagement becomes difficult, if not impossible. Nonetheless, engagement and collaboration is in everyone’s interest, in particular students and academics, who currently appear to be the main victims.